KEIKUTSERTAAN DALAM PELAKSANAAN IMUNISASI MR DI WILAYAH KERJA PUSKESMAS PIYUNGAN BANTUL YOGYAKARTA - Julia Rahma; Endah Tri Wahyuni (LPPM STIKES Madani Yogyakarta, 2019)
Puskesmas Piyungan is one of the Health Centers located in the Bantul Regency area of Yogyakarta. If we see from the geographical location, the distance of Piyungan Health Center with STIKES Madani Yogyakarta ranges around 7 KM. Considering the proximity of the area that is easily accessible, therefore STIKES Madani Yogyakarta is necessary to be involved in various activities within the health center working area of Puskesmas Piyungan and vice versa. the extensive working area of the health center needs participation of STIKES Madani HR in implementing government programs one of which is MR immunization due to the equity of the program implementation within the coverage area. The method used in community service activities is counseling about MR and direct provision of MR immunization. This activity was conducted in 3 namely A Alif, Klenggotan and Muhammadiyah Karangploso elementary schools for all classes 1 to 6. The implementation of counseling went well. Not only were the children participating, but the parents who were present at the time were also enthusiastic in participating in the counseling. The MR immunization process was managed in a team. Based on the results obtained qualitatively, some children and parents admitted that they were happy with the program because they were increasingly understanding about MR immunization and its benefits and at the same time were immediately given immunization as the prevention action.